Drug targets and predictive biomarkers in the management of metastatic melanoma - Thumar J; Giesen E; Kluger HM (Dove Medical Press, 2012)
Jaykumar Thumar, Eva Giesen, Harriet M KlugerYale Cancer Center, Yale School of Medicine, New Haven, CT, USAAbstract: Melanoma is the leading cause of fatal skin cancer, and in the past few decades, there has been an increase in the incidence of and mortality from metastatic melanoma. Until recently, the therapeutic options for treatment of metastatic melanoma were limited. The approval of ipilimumab (an anti-CTLA-4 antibody) and vemurafenib (mutant B-RAFV600E kinase inhibitor) by the Federal Drug Administration has led to a new era in melanoma treatment, and additional promising drugs and drug combinations are currently being investigated. As the choices of treatment for melanoma have expanded, the need to identify predictive biomarkers to tailor treatment strategies to individual tumor or immune system characteristics has become necessary. Such strategies have the potential of maximizing antitumor effect while minimizing toxicity and improving clinical benefit. In this article, we review the currently approved targeted therapies in melanoma and discuss the future of personalized therapy for this disease.Keywords: vemurafenib, mutations, inhibitors, tumors